Multi-Dimensional Sustainability Assessment Tool for Smallholder Farming Systems (MSAT) - Kumar, Shalander; Pramanik, Soumitra (2024)
• Nearly 500 million farmers are smallholders, producing ~80% of food in Asia and Sub-Saharan Africa. • Smallholder mixed farming systems operate within complex socio-economic and environmental contexts, presenting both opportunities and challenges. • The smallholder farming systems are highly heterogeneous, vulnerable, and face a multitude of challenges. • Hence, there is a need for a multidimensional understanding of these farming systems to design and promote sustainable intensification strategies.